ANALISIS PENDIDIKAN DAN PENGAJARAN DALAM AL-QUR’AN - Suhaili, Ridwan; charles, charles; Harvius, Harvius (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2022)
Education and teaching is one of the needs that must be met by every human being as God's creation. Likewise, the verses of the Qur'an were sent down by Allah, there are problems with education and teaching. The study of the interpretation of the Qur'an has experienced rapid development. Many methods and approaches used in analyzing the Qur'an include semantics. This study examines the field of education and teaching semantics from a semantic perspective promoted by Toshihiko Izutsu. The object of study in this research is the verses of the Qur'an concerning education and teaching. The results of the research show that the concept of education practiced by pre-Islamic, Islamic and after the revelation of the Qur'an underwent a change in meaning. Education, which in Arabic is translated as tarbiyah, used to be interpreted as nurturing or caring, experiencing an expansion of meaning, including teaching activities aimed at enabling students to develop their own potential, skills and noble character.